An Evaluation of the Gender Gap between Islamic Law and Practice from an Anthropological Perspective on Female Share in Inheritance: A Case Study from Pakistan - Muhammad Asad Latif (MAQOLAT: Journal of Islamic Studies, 2024)
The people in many developing nations are unable to exercise their fundamental human rights. Most women are not allowed to enter, own, or inherit land or other property. As a result, they are unable to purchase land. They become reliant on healthy marriage and family relationships as a result of this deprivation. Everybody has the legal and highly legitimate right to inherit, and Islam has explicitly granted this right to women. Unfortunately, Pakistani tradition differs from Islamic custom in this regard. The main goal of this study is to identify the factors that prevent women from inheriting property. The quantitative research approach has been used to achieve the research's aims. Four public universities in Bahawalpur and Lahore underwent a study. The survey was employed as a research technique. Students and instructors with advanced degrees were chosen for the data collecting. This data was subsequently examined to derive the study's conclusions. The study focuses on two key areas. According to poll results, women are denied their religious right to inheritance even in the highly educated sector because of social, cultural, and economical concerns.